Investigation of energy absorption capabilities of compressed and uncompressed crushable foams - Shah, Qasim Hussain; Topa, Ameen (The Japan Society of Mechanical Engineers, 2015)
Compressed and uncompressed crushable foam blocks were subjected to projectile impact at low velocity to evaluate and compare the foam resistance against the projectile impact. Among many crushable foam applications their energy absorbing characteristics play a prominent role to secure the structures against impacting objects. In the present work numerical simulations using finite element hydrocode LS-DYNA were first carried out to study the crushable foam behaviour when subjected to the impact by steel projectiles moving at an average velocity of 48 ms-1. A number of experiments were conducted to validate the numerical modelling. In the numerical analysis the foam properties were based upon previous work on crushable foam (Shah and Topa, 2014). It was found that the projectile impact on compressed foam, enhanced resistance against projectile penetration. Compressing the foam increases its density which results in an increase in the rate of energy absorption per unit time.